1976
DOI: 10.1073/pnas.73.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of viral-chemical co-carcinogenesis in vitro by type-specific anti-viral antibody.

Abstract: Low passage Fischer rat embryo cultures, which are normally very resistant to transformation by 3-methyicholanthrene but are highly susceptible when chronically infected with the Rauscher murine leukemia virus, were completely protected from transformation by methylcholanthrene when treated with neutralizing antiby specific for the leukemia virus prior to and during treatment with methylcholanthrene. Sister cultures were not protected by neutralizing antibody specific for the B-tropic radiation leukemia virus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The essential nature of leukemia virus infection in cocarcinogenesis was indicated by the failure of the virus to transform the cells when added after chemical treatment (Price et al, 1973). Furthermore, it has been demonstrated that cordycepin and typespecific anti-RLV antisera also inhibit co-carcinogenesis (Price et al, 1975(Price et al, , 1976. However, relatively little systematic experimentation has been performed to elucidate the specific role of viral components in this system.…”
mentioning
confidence: 99%
“…The essential nature of leukemia virus infection in cocarcinogenesis was indicated by the failure of the virus to transform the cells when added after chemical treatment (Price et al, 1973). Furthermore, it has been demonstrated that cordycepin and typespecific anti-RLV antisera also inhibit co-carcinogenesis (Price et al, 1975(Price et al, , 1976. However, relatively little systematic experimentation has been performed to elucidate the specific role of viral components in this system.…”
mentioning
confidence: 99%
“…Price and his associates (21) recently reported the prevention of carcinogen-induced malignant transformation of rat cells in vitro with the use of specific antiviral IgG prior to treatment with carcinogenic chemicals. This and other successful experiments in which Price and his associates employed both typespecific and heterotypic viral neutralizing antisera for suppression of both virus and transformation provided definitive evidence for the existence of virus specific determinants for transformation, because only type-specific antibodies against virus prevented transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, RIFRE cells detect a carcinogen-induced early event, survival in aggregation, that eventually progresses to neoplastic transformation. These data also confirm the results of carcinogen-induced transformation of RIFRE cells by others using more traditional methodology [Freeman et al, 1973b[Freeman et al, , 1975Price et al, 1971;Traul et al, 1981al. Previous studies have shown that nontransforming retroviruses play a significant and specific role in promoting the expression of transformation [Freeman et al, 1973a,c;Price et al, 1972aPrice et al, , 1976Price et al, , 1977Fisher and Weinstein, 19801. Low population doublings of Fischer rat embryo cell cultures were resistant to spontaneous transformation, chemically induced transformation, or transformation by murine retroviruses [Price et al, 1972a;Price and Mishra, 19801; cultures chronically infected with retrovirus had an increased sensitivity to transformation by chemical carcinogens.…”
mentioning
confidence: 99%